Identification and Preliminary Use of Recombinant Lambda gt11 Fusion Proteins in Human Cytomegalovirus Diagnosis - Ripalti, A.; Landini*, M. P.; Mocarski, E. S.; La Placa, M. (Journal of General Virology, 1989)
Summary We have isolated reactive clones from a λgt11 expression library of human cytomegalovirus (HCMV) DNA using HCMV-positive human sera. Among the recombinant clones obtained, one carried a fragment encoding a portion of p52, the major non-structural DNA-binding protein of 52K (p52) and another carried a part of the gene coding for p150, the major structural phosphoprotein. These two fusion proteins were examined by immunoblot analysis to test their ability to bind specific antibodies in human sera. The results showed that high titres of antibody to the DNA-binding protein are present in sera of patients undergoing acute HCMV infection, whereas high titres of antibodies to the structural phosphoprotein are widespread in the healthy HCMV-seropositive population. The use of these fusion proteins as antigens for differential screening of serum as a way of detecting recent HCMV infection is discussed.
Keywords: cytomegalovirus